Solubility of 2, 2′, 4, 4′, 6, 6′-hexanitrostilbene in binary solvent of N, N-dimethylformamide and acetonitrile. (April 2016) - Chen, Li-Zhen; Zhang, Tian-Bei; Li, Man; Li, Jing; Cao, Duan-Lin
Highlights: The solubility of HNS in DMF + ACN system were measured by the laser monitoring system. The experimental solubility values of HNS were correlated by three correlation models. The standard dissolution enthalpy, standard entropy and standard Gibbs energy were calculated. Abstract: The solubility of 2, 2′, 4, 4′, 6, 6′-hexanitrostilbene (HNS) in binary solvents of (N, N-dimethylformamide + acetonitrile) was measured using a laser monitoring observation technique. In this study, the solubility of HNS in (DMF + CAN) mixtures was measured over the temperature range from (298.15 to 338.15) K under atmospheric pressure. From the experimental results, the solubility of HNS in DMF was found to increase with increasing temperature and mass fraction of DMF. The experimental values were correlated with the CNIBS/R–K model, modified Apelblat equation and Jouyban–Acree model. The effect of solvent composition and temperature on the solubility was discussed. The standard dissolution enthalpy, standard dissolution entropy and the Gibbs energy were calculated according to the experimental solubility data. The solubility data, correlation equations and thermodynamic property obtained from this study would be invoked as basic data and models regarding the crystallization process of HNS.